Darba samaksas organizācija uzņēmumā SIA "Palink" - Kārkliņa, Liene (Latvijas Universitāte, 2014)
Bakalaura darba temats ir „Darba samaksas sistēma un tās organizēšana SIA „Palink”. Bakalaura darba mērķis ir izpētīt un aprakstīt darba samaksas sistēmu un tās organizēšanu Latvijā un SIA „Palink”, un izanalizēt statistikas datus par darba samaksu Latvijā laika periodā no 2009. gada līdz 2013. gadam. Darba izstrādes gaitā autore secināja, ka darba samaksas sistēma un tās organizēšana SIA “Palink” notiek saskaņā ar LR normatīvo aktu prasībām. Bakalaura darba atslēgvārdi – Darba likums, darba samaksa, alga, pieaugums, bruto, darbinieks, darba devējs, uzskaite. Bakalaura darbs apjoms ir 66 lappusēm un tas satur 4 pielikumus, 4 tabulas, 20 attēlus.

The theme of the Bachelor’s paper is The System of Payroll and its Organization in the Company Palink, Ltd. The aim of the paper is to explore and describe the system of Payroll and its organization in Latvia and in Palink Ltd. and to analyse statistical data about wages in Latvia in the period of time from the year 2009 until 2013. Having done the research, the author of the paper has concluded that the system of wages and its organization in Palink Ltd. is done according to the requirements of the normative acts in the Republic of Latvia. The keywords of the bachelor’s paper are the following: labour law, wages, salary, increase, gross, employee, employer, accounting. The bachelor’s paper consists of 66 pages and it contains 4 attachments, 4 tables, and 20 images.
Payroll organization at "Palink" Ltd
Keywords: Vadībzinātne